Recent Advances in Applied Microbiology and Food Sciences, Volume II - Przemysław Łukasz Kowalczewski; Miroslava Kačániová (Applied Sciences, 2023)
The food industry is constantly evolving due to environmental, social, and geopolitical factors [...]